2018
DOI: 10.1136/bmjopen-2018-024503
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ attendance patterns to different healthcare settings and perceptions of stakeholders regarding screening for chronic, non-communicable diseases in high street dental practices and community pharmacy: a cross-sectional study

Abstract: ObjectiveNon-communicable diseases (NCDs) impose a significant health and economic burden. This study aimed to assess the differential attendance patterns of public to different healthcare professionals and gauge the opinions of key stakeholders towards screening of NCDs by allied healthcare professionals.DesignQuestionnaires were designed piloted and subsequently completed by key stakeholders. The results were analysed descriptively.SettingPublic questionnaires were undertaken in a West Midlands transport sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 20 publications
3
30
0
Order By: Relevance
“…Furthermore, among patients there was strong support for tests which were able to yield immediate results. These findings appeared to transcend specific healthcare systems and cultural barriers, as similar results were reported irrespective of their being conducted in different countries with different models of healthcare provision, including state-funded healthcare systems in Europe [39][40][41], insurance-based and private healthcare within the USA [33] and university-based clinics and private settings in Asia [36].…”
Section: Opinions Of Key Stakeholderssupporting
confidence: 62%
See 1 more Smart Citation
“…Furthermore, among patients there was strong support for tests which were able to yield immediate results. These findings appeared to transcend specific healthcare systems and cultural barriers, as similar results were reported irrespective of their being conducted in different countries with different models of healthcare provision, including state-funded healthcare systems in Europe [39][40][41], insurance-based and private healthcare within the USA [33] and university-based clinics and private settings in Asia [36].…”
Section: Opinions Of Key Stakeholderssupporting
confidence: 62%
“…Among studies that asked patients whether they felt it was "important" that dentists identify individuals at high risk of T2DM, patient support was strong, in a range of 73%-87% [33,35,36,[39][40][41]. In addition to this acknowledgement, most patients surveyed were willing to undergo chairside screening methods that yielded immediate results and discuss the results of such tests with their dentist [35,36,39,40].…”
Section: Resultsmentioning
confidence: 99%
“…A study undertaken in the UK found 12% of people claiming to attend dental appointments at 6‐monthly intervals also stated they had not had contact with their GP in the same 12‐month period [19]. Furthermore, of the sample that identified as regular dental attenders, almost half claimed to have never had an NHS health check at their GP surgery [19]. As ~ 60% of the UK adult population are registered with a dentist [20], this places dental teams in a strong position to identify individuals for risk‐based assessments, as they have access to people who would not necessarily attend their GP regularly when asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from the USA suggests that, in 2008, 24% of people did not have contact with a general healthcare provider, yet 23% of those accessed a dentist during that time [5]. This was also reported for a UK population, where 12% of patients who reported seeing a dentist biannually reported they had not had contact with a GP in the same 12-month period [3]. Furthermore, 48% of those who reported being regular dental attenders advised having never had a health check at their GP surgery [3].…”
Section: Introductionmentioning
confidence: 82%
“…Allied healthcare professionals in the UK access large proportions of the population who frequently do not access general medical practice [GP] services [3]. Given the growing NCD burden, this study aimed to determine patient acceptability and potential barriers to utilising allied healthcare professionals such as dentists and pharmacists in order to assist GPs with the NCD epidemic, through targeted risk-based assessment and early detection.…”
Section: Introductionmentioning
confidence: 99%